Challenges of Patent Protection in the Digital Era: Analysis of Indonesian Law and Comparison with the Patent Protection Model in China - Vivian, Vivian; Aprilia, Aliyyah; Fiqih, Geizka Orillia; Disemadi, Hari Sutra (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
The development of digital technology has increased the number of patent infringements globally, while the patent protection system in Indonesia is still unable to accommodate digital dynamics. Regulatory backwardness, slow bureaucracy, and low public awareness are the main obstacles in patent protection. This study aims to analyze and compare the patent protection systems of Indonesia and China in facing the challenges of the digital era. This study uses a normative legal method with a comparative law approach based on Schlesinger's theory, with descriptive-qualitative analysis through a study of regulatory literature and related legal documents. The study shows that Indonesia faces serious challenges such as the length of the patent registration process, weak law enforcement, and the non-recognition of patents for software and algorithms. On the other hand, China has established a progressive digital patent protection system, including a special IPR court, an integrated digital evidence system, and a blueprint for an IP protection strategy until 2035. China's system also adopts an efficient approach to patent examination, with a duration of only 15 months compared to Indonesia's 3-5 years. Both countries refer to the TRIPS standard, but their implementation is very different due to varying institutional capacities and country strategies. Indonesia is advised to carry out legal reforms and strengthen public education to support patent protection that is adaptive to the digital era.